INTERGENERATIONAL DYNAMICS IN LANGUAGE AND LITERACY: THE INFLUENCE OF GRANDPARENT AND PARENT-CHILD INTERACTIONS ON EARLY CHILDHOOD DEVELOPMENT - Ting, Zhang; Masran, Md Nasir; Omar, Romarzila; Yang , Wenjun (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Early childhood development in language and literacy is influenced by interactions with caregivers. This study examines the differential impacts of grandparent and parent-child interactions on these developmental outcomes using a qualitative approach. Semi-structured interviews were conducted with 30 families, including both grandparents and parents of children aged 2 to 5 years, focusing on the nature and frequency of interactions and their perceived impact on children’s language and literacy development. The qualitative data revealed distinct interaction styles between grandparents and parents, with grandparents often engaging in storytelling and cultural transmission, while parents focused on structured learning activities. Both types of interactions were perceived to contribute uniquely to children’s development. These findings underscore the significant influence of intergenerational interactions on early childhood development, suggesting the need for educational interventions and policies that consider the full range of family dynamics.